2023
DOI: 10.1007/s00520-023-08063-0
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of self-efficacy between social constraints, social isolation, family environment, and depressive symptoms among breast cancer patients in China: a cross-sectional study

ZhiHui Gu,
MengYao Li,
Li Liu
et al.

Abstract: Background: For female breast cancer patients, the psychological status after surgery, especially the social and family psychological related factors, deserves more attention. This study analyzed the in uence of social constrain, social support, social isolation, family con ict, family emotion expression on depression. At the same time, this study conducted the relationship between the variables and the mechanism of action.Methods: 522 breast cancer patients nished questionnaires consisting of Self-Rating Depr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
1
1
Order By: Relevance
“…Furthermore, the Second Hypothesis is known that the Social Environment variable has a significant positive effect on Self Efficacy, the p-value of 0.158 (>0.05) and the t-value of 1.413 (<1.96) indicates an insignificant relationship. These results are not in line with previous research conducted by (Botha & Steyn, 2022;Chairat Rais & Ayu Rachmawati, 2019;Chiengkul et al, 2023;Gu et al, 2023;Morgan & Doku, 2023) with the results of their research which states that the Social Environment influences Self Efficacy. These results indicate that the better the Social Environment in entrepreneurship, it does not have an impact on Self-efficacy as a supporter of entrepreneurship.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the Second Hypothesis is known that the Social Environment variable has a significant positive effect on Self Efficacy, the p-value of 0.158 (>0.05) and the t-value of 1.413 (<1.96) indicates an insignificant relationship. These results are not in line with previous research conducted by (Botha & Steyn, 2022;Chairat Rais & Ayu Rachmawati, 2019;Chiengkul et al, 2023;Gu et al, 2023;Morgan & Doku, 2023) with the results of their research which states that the Social Environment influences Self Efficacy. These results indicate that the better the Social Environment in entrepreneurship, it does not have an impact on Self-efficacy as a supporter of entrepreneurship.…”
Section: Discussioncontrasting
confidence: 99%
“… 19 , 20 When faced with the same source of stress, individuals with high self-efficacy adopted different corresponding strategies, which in turn affected healthy behavior. 21 , 22 Studies on college students have shown that self-efficacy played a positive role in the relationship between physical activity and internet addiction. 23 However, there was no research to confirm that self-efficacy can moderate the impact of pregnancy stress on smartphone addiction.…”
Section: Introductionmentioning
confidence: 99%